将 $a^3+b^3+c^3-3abc$ 因式分解.
\[
a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-bc-ca).
\]
\[
a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-bc-ca).
\]
1
Note that
\[
(a+b)^3=a^3+3a^2b+3ab^2+b^3,
\]
故
\[
a^3+b^3=(a+b)^3-3ab(a+b).
\]
于是
\[
\begin{split}
a^3+b^3+c^3-3abc&=\bigl[(a+b)^3-3ab(a+b)\bigr]+c^3-3abc\\
&=(a+b)^3+c^3-3ab(a+b)-3abc\\
&=\Bigl[(a+b+c)^3-3(a+b)c(a+b+c)\Bigr]-3ab(a+b+c)\\
&=(a+b+c)\Bigl[(a+b+c)^2-3(a+b)c-3ab\Bigr]\\
&=(a+b+c)(a^2+b^2+c^2+2ab+2bc+2ca-3ab-3bc-3ca)\\
&=(a+b+c)(a^2+b^2+c^2-ab-bc-ca).
\end{split}
\]